2015
DOI: 10.18632/oncotarget.5189
|View full text |Cite
|
Sign up to set email alerts
|

CDK1 phosphorylation of TAZ in mitosis inhibits its oncogenic activity

Abstract: The transcriptional co-activator with PDZ-binding motif (TAZ) is a downstream effector of the Hippo tumor suppressor pathway, which plays important roles in cancer and stem cell biology. Hippo signaling inactivates TAZ through phosphorylation (mainly at S89). In the current study, we define a new layer of regulation of TAZ activity that is critical for its oncogenic function. We found that TAZ is phosphorylated in vitro and in vivo by the mitotic kinase CDK1 at S90, S105, T326, and T346 during the G2/M phase o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 61 publications
2
30
0
Order By: Relevance
“…As expected, the mobility of KIBRA, YAP, and TAZ were all significantly retarded due to phosphorylation during G2/M arrest (Fig. 1A) (12,15,30,31). Taxol or Nocodazole treatment did not cause any evident change in the mobility/phosphorylation for PTPN14, NF2, or EX (which are all upstream regulators of the Hippo-YAP pathway), for WW45 or TEAD1 (Fig.…”
Section: Resultssupporting
confidence: 73%
See 4 more Smart Citations
“…As expected, the mobility of KIBRA, YAP, and TAZ were all significantly retarded due to phosphorylation during G2/M arrest (Fig. 1A) (12,15,30,31). Taxol or Nocodazole treatment did not cause any evident change in the mobility/phosphorylation for PTPN14, NF2, or EX (which are all upstream regulators of the Hippo-YAP pathway), for WW45 or TEAD1 (Fig.…”
Section: Resultssupporting
confidence: 73%
“…Interestingly, we also found that several Hippo core members (Lats1, Lats2, and Mst2) (Fig. 1) or their upstream regulator (KIBRA) (30,31) or downstream effectors (YAP and TAZ) (12,13,15) are phosphorylated during mitosis. Importantly, mitotic phosphorylation is critical for their oncogenic or tumor suppressive functions (12,13,15).…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations